2010
DOI: 10.1080/00207591003774493
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the motivation jungle: Predicting performance on a novel task by investigating constructs from different motivation perspectives in tandem

Abstract: Different theoretical viewpoints on motivation make it hard to decide which model has the best potential to provide valid predictions on classroom performance. This study was designed to explore motivation constructs derived from different motivation perspectives that predict performance on a novel task best. Motivation constructs from self-determination theory, self-regulation theory, and achievement goal theory were investigated in tandem. Performance was measured by systematicity (i.e. how systematically st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 19 publications
1
9
0
1
Order By: Relevance
“…The results obtained from the present study is in harmony with the previous research in the fields of education and psychology (Bidjerano & Dai, 2007;Pintrich, et al, 1993;Van Nuland, et al, 2010; ) which shows that effort regulation strategies are closely related to successful performance. Van Nuland, et al, (2010) and Komarraju and Nadler (2013) demonstrated that successful learners use more effort regulation strategies in their learning.…”
Section: Journal Of Language Teaching and Researchsupporting
confidence: 79%
See 1 more Smart Citation
“…The results obtained from the present study is in harmony with the previous research in the fields of education and psychology (Bidjerano & Dai, 2007;Pintrich, et al, 1993;Van Nuland, et al, 2010; ) which shows that effort regulation strategies are closely related to successful performance. Van Nuland, et al, (2010) and Komarraju and Nadler (2013) demonstrated that successful learners use more effort regulation strategies in their learning.…”
Section: Journal Of Language Teaching and Researchsupporting
confidence: 79%
“…Van Nuland, et al, (2010) and Komarraju and Nadler (2013) demonstrated that successful learners use more effort regulation strategies in their learning.…”
Section: Journal Of Language Teaching and Researchmentioning
confidence: 99%
“…'I'm curious to know how I can apply these skills again'). This scale was validated in a similar context (Van Nuland et al, submitted for publication; Van Nuland et al 2010). Cronbach's α of this subscale was 0.86 in experiment 1 and 0.87 in experiment 2.…”
Section: Motivationmentioning
confidence: 99%
“…Intrinsic motivation represents a drive from within instead of external pressure. Though self-determination theory is not unanimously adhered to, the positive effects of this type of motivation are currently broadly agreed upon and are hardly subject to debate (e.g., Alexander & Murphy, 1998;Brophy, 2004;Hidi, 2001Hidi, , 2006Martens, Gulikers, & Bastiaens, 2004;Schunk et al, 2008;van Nuland, Dusseldorp, Martens, & Boekaerts, 2010).…”
Section: Conceptualizations Of Task-specific Motivationmentioning
confidence: 99%